A Low-Grade Myxoid Liposarcoma Arising in a Deep-Seated Conventional Lipoma. (December 2019) - Tsagkozis, Panagiotis; Haglund, Felix
Myxoid liposarcomas (MLS) are known to arise de novo and have not been shown to derive from previous benign lesions (lipomas), whereas lipomas occasionally harbor areas of other benign mesenchymal tissue. Rarely, tumors presenting with MLS or round cell liposarcomas together with conventional liposarcoma have been classified as mixed liposarcomas. However, no case of MLS arising in a conventional lipoma has been described. In this article, we report a case of a young male presenting with a deep-seated soft tissue tumor of the posterior part of the thigh. The tumor was removed en bloc. Grossing revealed a small encapsulated myxoid lesion (2.5 cm) within the larger lipomatous tumor (14 cm). Histological examination and cytogenetic analysis revealed a FUS-CHOP positive low-grade MLS arising in a conventional lipoma without histological atypia, FUS-CHOP fusion, or CDK4/MDM2 amplification. While we cannot conclude whether these were collision tumors or an MLS progression from a lipoma, this case highlights the value of careful grossing in the soft tissue setting.